Tantangan Regulasi Pajak Bagi UMKM Di Era Digitalisasi: Perspektif Hukum bagi Perwujudan SDGs - Dedi Jaya; Winsherly Tan; Ampuan Situmeang (Universitas Cokroaminoto Yogyakarta, 2026)
Digitalization of tax administration serves as a strategic juridical instrument to optimize state revenue for accelerating 2030 SDG targets. This research analyzes legal problematics in MSME taxation within the digital era. The study examines: 1) MSME tax regulation reconstruction; 2) implementative juridical obstacles; and 3) policy formulation for legal compliance. Utilizing a normative-juridical method with a legal development theory approach, findings indicate that Law No. 7/2021 and Government Regulation No. 55/2022 establish a legal basis for strengthening the digital tax base. However, a discrepancy persists between norms and implementation due to inadequate legal dissemination. Therefore, policy reorientation through massive socialization and regulatory simplification is necessary to enhance public legal compliance in support of sustainable development.